Konsep Ketuhanan Perspektif Ibn Arabi - Ibnu Chudzaifah; Muh. Muhyiddin; Afroh Nailil Hikmah (LPPM IAIN Sorong, 2022)
One of the main themes that have always received attention in the history of human thought is the problem of divinity. This theme is discussed not only in the world of philosophy and theology, but also in the mystical world. This theme is never dryly discussed in order to find concepts and efforts that should be suitable for carrying out various approaches to religious concepts. Philosophy, which starts from the ratio with its enrichment, is rooted in the deepest depths of the nature of things. In this article, we will discuss a brief biography of Ibn Arabi, the method of Ibn Arabi's approach, makrifat about worry and istiqra ', an ontological review of the nature of the names of God, Ibn Arabi's concept of divinity. The approach taken by Ibn Arabi is not much different from the approach of other mystics, namely both emphasizing the kasyf approach. However, Ibn Arabi was able to use his basic philosophy to describe his mystical experiences. Attempting to describe mystical experiences is not an easy thing without the help of active reasoning. It is not surprising that Ibn Arabi's theosophical school always tries to turn on the imagination in describing mystical experiences, especially about God in a sense that simultaneously leads to his transcendence and immanence. The mystical-style approach taken by Ibn Arabi is nothing but a form of transferring the